Factorial Study on the Effects of β-Cyclodextrin and Surfactants on the Solubility and Dissolution Rate of Carbamazepine - Chowdary, K.P.R.; Srinivasa Reddy, K. (Asian Journal of Chemistry, 2010)
Carbamazepine, a widely used anticonvulsant drug belongs to class II under BCS and exhibit low and variable oral bioavailability due to its poor aqueous solubility. In the present study the individual main effects and combined (or interaction) effects of β-cyclodextrin (βCD) and two surfactants (Tween 80 and sodium lauryl sulphate) on the solubility and dissolution rate of carbamazepine were evaluated in a series of 22 factorial experiments. The individual main effects of βCD, Tween 80 and sodium lauryl sulphate (SLS) and combined effect of βCD and SLS in enhancing the solubility of carbamazepine were significant (p < 0.05). The solubility of carbamazepine was markedly enhanced by βCD (2.06 folds), Tween 80 (2.72 folds) and SLS (31.76 folds). Combination of βCD and SLS gave a 48.53 fold increase in the solubility of carbamazepine. Carbamazepine-βCD-surfactant binary and ternary systems were prepared by kneading method and were evaluated for dissolution rate and dissolution efficiency (DE30) as per a 22 factorial design. The dissolution of carbamazepine was rapid and higher from the binary and ternary systems prepared employing βCD and surfactants when compared to carbamazepine pure drug. β-Cyclodextrin alone gave higher enhancement in K1 (2.349 folds) and DE30 (4.247 folds) of carbamazepine. The individual main effects of βCD and SLS and the combined effect of βCD and SLS in enhancing the K1 of carbamazepine were significant (p < 0.05).